An evaluation of the impacts of health insurance coverage on wealth stratification in some selected sub-Saharan countries - Amaama Abdul Malik; Muhittin Kaplan (Health Economics Review)
Abstract Background Health is a crucial component of an economy, influencing the performance of various sectors. As a result, nearly every country has implemented health policies to achieve the United Nations Development Goals and Universal Health Coverage (UHC) targets, which focus on providing universal access to necessary, sufficient, and quality healthcare without financial barriers. Implementing such policies in the sub-Saharan region led Burundi, Gabon, Ghana, and Rwanda to emerge as the only four countries in the region to have healthcare coverage over 20%. This study sought to investigate whether the health insurance policies implemented impact the wealth stratification of households in these countries. Methods The study used data from the sub-Saharan region section of the Demographic and Health Surveys (DHS) Program by the U.S. Agency for International Development (USAID) with Robust Ordered Probit Estimation Technique. Results The results show that health insurance negatively impacts the Wealth levels of those in the poorest, poorer, and middle-income levels in Burundi and Rwanda more than those in the wealthiest group. Community-based insurance in Gabon and national health insurance in Ghana positively impact the income of lower households. Conclusions The government should improve social amenities, especially in rural areas. Also, the study identified limited information as one reason for the outcome. We propose increasing education on the importance of health and the benefit package when one subscribes to a health insurance scheme to encourage patronage and decrease out-of-pocket expenditure.